Pendampingan Penerangan Jalan Umum (PJU) Berbasis Tenaga Surya dan LED di Desa Jatiwates Kecamatan Tembelang (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
One of the problems faced by Jatiwates Village is the low level of community skills in maintaining and operating PJU which has an impact on the operation of PJU not being as it should. Therefore, assistance is needed so that the community can operate PJU properly. The purpose of this activity is to improve community skills in maintaining and operating PJU street lights based on solar and LED energy that are independent without the help of electricity. This activity was carried out on October 10, 2022, in Jatiwates Village, Tembelang District, Jombang Regency. The method used in this activity is Participatory Action Research (PAR), which consists of three stages, namely planning, implementation and evaluation. The results of the activity show that the community can operate PJU according to the assistance that has been provided. The output of this activity is a ready-to-use and ready-to-use product in the form of solar-based PJU..